Separation and detection of Gram-negative bacteria via vancomycin-functionalized magnetic beads and aminopeptidase test strips - Xu, Xiao; Zhu, Anji; Bai, Lixia; Li, Shihong; Ge, Wenbo; Yang, Yajun; Liu, Xiwang; Qin, Zhe; Li, Zhun; Li, Jianyong (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionGram-negative bacteria are key pathogens causing food contamination and animal diseases (such as bovine mastitis), and they are prone to developing multidrug resistance, necessitating rapid and sensitive detection technologies.MethodsWe developed a novel detection method based on an antibiotic affinity strategy, which combines vancomycin-functionalized magnetic beads (Van-MBs) with aminopeptidase test strips. Vancomycin, which binds exclusively to D-alanyl-D-alanine (D-Ala-D-Ala) on the cell wall of Gram-positive bacteria, is used by Van-MBs to capture Gram-positive bacteria from the sample. After magnetic separation, the supernatant containing Gram-negative bacteria is retained. This supernatant reacts with aminopeptidase test strips, utilizing the enzyme's unique properties as a Gram-negative enzyme. Visual detection is made possible by the enzyme's catalysis of the chromogenic substrate, which produces a yellow signal.ResultsUsing raw milk as a representative sample, validation showed that the approach achieves a detection limit of 1.0 × 101 CFU/mL within 100 minutes.DiscussionThis approach is quick, sensitive, and visual, and it doesn't require complicated equipment. It also offers useful technical support for safe food production, early animal disease detection, and sensible antibiotic administration.